Telemedicine and E-health services, policies, and applications advancements and developments - Rodrigues, Joel 1972-; Torre Diez, Isabel de la; Sainz de Abajo, Beatriz 1974- (Premier reference source, 2012)
"This book offers a comprehensive and integrated approach to telemedicine by collecting E-health experiences and applications from around the world and by exploring new developments and trends in medical informatics" - Provided by publisher